The Concept of Flexible Lower Limb Powered-Exoskeleton for Human Performance Augmentation: A Review - Md Zain, Badrul Aisham (International Journal of Integrated Engineering, 2024)
This review covers the lower limb powered exoskeleton by using the two-links flexible to generate the dynamic model for flexible robotic legs. The exoskeletons are defined as wearable robotic mechanisms for carrying loads. Therefore, this paper covers various aspects of two-flexible links in term of modeling methods, dynamical analyses, and control schemes. An introduction to PID controller at the short literature review is provided to improve the performance of flexible robotic legs. This review summarizes the overview of augmenting exoskeletons, types of lower limb exoskeletons, biomechanics of human gait, the mathematical models of two-flexible link, and the control approach of the two-link flexible to generate flexible lower limb powered exoskeleton for carrying load based on the concept of two-link flexible.